Rebuilding crime prevention through environmental design: strengthening the links with crime science - Armitage, Rachel; Ekblom, Paul (Crime science series, 2019)
Cover; Half Title; Series; Title; Copyright; Contents; List of figures; List of tables; Foreword; Acknowledgements; List of contributors; 1 Introduction; 2 Moving home as a flight from crime: residential mobility as a cause and consequence of crime and a challenge to Crime Prevention Through Environmental Design; 3 "Why my house?" -- exploring the influence of residential housing design on burglar decision making; 4 Using guardianship and situational crime prevention (SCP) to strengthen Crime Prevention Through Environmental Design (CPTED)